2022
DOI: 10.1002/slct.202201504
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Molecular Packing study of Three New Amidophosphoric Acid Esters and Assessment of Their Inhibiting Activity Against SARS‐CoV‐2 by Molecular Docking

Abstract: Three new compounds of amidophosphoric acid esters with a [OCH2C(CH3)2CH2O]P(O)[X] segment (where X=cyclopentylamido (1), 2‐aminopyridinyl (2) and pyrrolidinyl (3)) were synthesized and studied using FT‐IR and 31P/13C/1H NMR spectroscopies and single‐crystal X‐ray diffraction analysis. The compounds crystallize in the triclinic space groups Ptrue1‾ for 1 and 3 and in the orthorhombic space group Pca21 for 2, where the asymmetric unit consists of three symmetrically‐independent molecules for 1 and one molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
(103 reference statements)
2
3
0
Order By: Relevance
“…In this esteric ring, the P═O bond is located in a position intermediate between equatorial and axial (with angles O P O –P−O estric = 113.68 (7)° and 114.39 (7)°, O P O –P–N = 115.15 (8)° and O estric −P–N = 105.43 (9)° and 104.30 (8)°). Such an intermediate position of the P═O bond has also been observed for similar amidophosphoric acid esters with a tertiary mine [ 27 ].…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…In this esteric ring, the P═O bond is located in a position intermediate between equatorial and axial (with angles O P O –P−O estric = 113.68 (7)° and 114.39 (7)°, O P O –P–N = 115.15 (8)° and O estric −P–N = 105.43 (9)° and 104.30 (8)°). Such an intermediate position of the P═O bond has also been observed for similar amidophosphoric acid esters with a tertiary mine [ 27 ].…”
Section: Resultssupporting
confidence: 58%
“…For 2 , the P═O, P–O and P–N bond lengths and O═P–N, O═P–O and O–P–N angles are similar to related compounds [ 27 , 51 ] ( Table S1 ). The tertiary amine N5 of this compound has a sp 2 hybridization and a planar configuration reflected in the sum of the surrounding angles (∠P–N–C + ∠P–N–C + ∠C–N–C) about 360° (360.0 (16)°).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The previously mentioned papers focus on structural and biochemical studies on compounds with potential pharmaceutical properties including anticancer 41 and antiviral activities. 42 In one study dedicated to protein–ligand interactions, it was found that ED polarization of the ligand molecule in the protein binding pocket could be used to predict the electrostatic features of the binding itself. However, these experimental results are difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%